2017
DOI: 10.1177/0018726717715075
|View full text |Cite
|
Sign up to set email alerts
|

A lifespan perspective for understanding career self-management and satisfaction: The role of developmental human resource practices and organizational support

Abstract: The contemporary career literature or ‘new career’ theory emphasizes the importance of individual agentic career management processes in which individuals manage their careers to achieve career satisfaction by flexibly adjusting to the dynamic environment. There is limited research, however, on how individuals strategize their careers as they age, by utilizing or balancing organizational career management factors, including developmental human resource (HR) practices and organizational support. This study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 107 publications
2
107
0
2
Order By: Relevance
“…First, it is important for individuals themselves because it is associated with greater life satisfaction and psychological well‐being (Nicholson & DeWaal‐Andrews, ; Rain, Lane, & Steiner, ); and second, it is important for organizations because subjective career success can lead to lower turnover intentions and more support for organizational change (Nauta, Vianen, Van der Heijden, Dam, & Willemsen, ). Our findings present interesting implications for these two careers' stakeholders, who today are expected to share the responsibility for career success, having to make difficult decisions about how much to invest in supportive organizational practices (Human Resource Development, supervisor support) on the one hand and how much to encourage proactive career self‐management on the other (De Vos et al, ; Jung & Takeuchi, ).…”
Section: Discussionmentioning
confidence: 90%
“…First, it is important for individuals themselves because it is associated with greater life satisfaction and psychological well‐being (Nicholson & DeWaal‐Andrews, ; Rain, Lane, & Steiner, ); and second, it is important for organizations because subjective career success can lead to lower turnover intentions and more support for organizational change (Nauta, Vianen, Van der Heijden, Dam, & Willemsen, ). Our findings present interesting implications for these two careers' stakeholders, who today are expected to share the responsibility for career success, having to make difficult decisions about how much to invest in supportive organizational practices (Human Resource Development, supervisor support) on the one hand and how much to encourage proactive career self‐management on the other (De Vos et al, ; Jung & Takeuchi, ).…”
Section: Discussionmentioning
confidence: 90%
“…The time must be no longer than 5 years. Regular and continuous evaluation of an employee in terms of meeting the goals set by plan is a part of the process [65,66].…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…Age management, as practiced in most organisations, focuses on all age categories and not isolating one specific age segment. A number of different studies found that targeting different age groups with different research concepts can impact on application of tools for support of employment development which are different in different age groups [56]. A study examining how career support tools are connected in relation to worker satisfaction levels showed that younger workers are more satisfied when the level of instruments is high, while in older age groups satisfaction is higher when support is lower [56].…”
Section: Selected Age Management Aspects Forming Competitive Advantagementioning
confidence: 99%
“…A number of different studies found that targeting different age groups with different research concepts can impact on application of tools for support of employment development which are different in different age groups [56]. A study examining how career support tools are connected in relation to worker satisfaction levels showed that younger workers are more satisfied when the level of instruments is high, while in older age groups satisfaction is higher when support is lower [56]. A separate study examining the relationship between flexible working time and performance concluded that formal measures allowing flexible work had a negative impact on performance but a positive effect on job satisfaction [57].…”
Section: Selected Age Management Aspects Forming Competitive Advantagementioning
confidence: 99%